When ‘Good’ Leadership Backfires : Dynamics of the leader/follower relation - Einola, Katja; Alvesson, Mats (Organization Studies, 2021)
This paper contributes to the understanding of relational aspects of leadership and followership. Our in-depth empirical study of the leader/follower relation uncovers how and why assigning team members into ‘leader’ and ‘follower’ positions may sometimes be a double-edged sword and lead to unintended consequences undermining both the team’s potential and member satisfaction. We report on a multi-voiced story of one team that at first looked like a well-performing one with effective, ‘good’ leadership and satisfied team members. However, a closer investigation revealed frictional understandings, unresponsiveness and dynamics of immaturization as the followers overly relied on the elected leader. Leadership seen as ‘good’ may indeed backfire and encourage satisfied, trustful followers to relax and focus on limited roles. Our study further shows the need to conduct rich empirical studies that capture views of all parties in a relation.
Keywords: followership; immaturization; leadership; process study; relational leadership; shared meanings; teams